2000
DOI: 10.1046/j.1471-4159.2000.0750908.x
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Genes for Neuropeptide Y and Peptide YY Reveal Origin by Chromosome Duplication from an Ancestral Gene Linked to the Homeobox Cluster

Abstract: Neuropeptide Y (NPY) and peptide YY (PYY) are related 36-amino acid peptides. NPY is widely distributed in the nervous system and has several physiological roles. PYY serves as an intestinal hormone as well as a neuropeptide. We report here cloning of the npy and pyy genes in zebrafish (Danio rerio). NPY differs at only one to four amino acid positions from NPY in other jawed vertebrates. Zebrafish PYY differs at three positions from PYY from other fishes and at 10 positions from mammals. In situ hybridization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 60 publications
2
31
0
1
Order By: Relevance
“…Rats submitted to chronic food restriction had differentially affected NPY gene expression in the hypothalamus and liver, suggesting that NPY expression may also be differentially regulated in other tissues (Sucajtys-Szulc et al 2008), while in fi sh it has not yet been demonstrated. Therefore, it may be risky to draw functional conclusions from anatomical studies in a single species (Soderberg et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Rats submitted to chronic food restriction had differentially affected NPY gene expression in the hypothalamus and liver, suggesting that NPY expression may also be differentially regulated in other tissues (Sucajtys-Szulc et al 2008), while in fi sh it has not yet been demonstrated. Therefore, it may be risky to draw functional conclusions from anatomical studies in a single species (Soderberg et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…All tetrapods have three related peptides, namely NPY, peptide YY (PYY) and pancreatic polypeptide (PP) (Cerdá-Reverter and Larhammar, 2000). The NPY and PYY genes are located adjacent to Hox clusters and presumably arose as a result of a chromosome duplication prior to the origin of gnathostomes (Soderberg et al, 2000;. PP is a duplicate of PYY in tetrapods (Larhammar et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that pancreatic polypeptide and PYY stimulate Y4 receptor function in peripheral organs and that central functions are signalled by NPY. However, it will be interesting to see if PYY and pancreatic polypeptide are present in the chicken CNS, as PYY is more abundant in the CNS in fishes (Cerda-Reverter & Larhammar 2000, Söderberg et al 2000 and lamprey (Söderberg et al 1994) than in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…NPY is extremely well conserved and has only one amino acid replacement between human and chicken, and four replacements between human and zebrafish (Blomqvist et al 1992, Larhammar 1996, CerdaReverter & Larhammar 2000, Söderberg et al 2000. PYY is more divergent, and pancreatic polypeptide differs greatly between species, with only 16 of 36 positions identical between human and chicken (Kimmel et al 1975, Larhammar 1996, Cerda-Reverter & Larhammar 2000.…”
Section: Introductionmentioning
confidence: 99%